Walking for fun or for "likes"? The impacts of different gamification orientations of fitness apps on consumers' physical activities. Issue 5 (November 2019) - Tu, Rungting; Hsieh, Peishan; Feng, Wenting
Highlights: Making the app "social" is more effective than making it "fun" in helping consumers sustain their efforts in physical activity. Consumers using the app focusing on social value showed better performance in walking and higher intentions to continue using the app. Fitness apps should help provide social value. Abstract: To effectively motivate consumers to continue exercising, many developers gamify the fitness apps, aiming at making work-outs more fun. However, the authors argue that making it fun may not be effective enough to motivate consumers to sustain their efforts. The authors propose that making the apps more social may provide better value and can be more effective in promoting consumers' participation in physical activity. A longitudinal study was conducted, and participants were recruited for the seven-week fitness-tracking study. Participants were randomly assigned to use one of the two apps: one with game elements focusing on enhancing emotional value (Walkup) and the other with elements focusing on increasing social value (WeChat Sports). Both apps recorded participants' daily step counts and tracked their physical activities. One week after the fitness-tracking study, participants' intentions to continue using the app were measured. The results indicate that, compared with the participants using Walkup (focusing on fun), those using WeChat Sports (focusing on social) showed better performance in step counts in each of the seven weeks, and higher intentions to continue exercising with the app. The results indicate that, even though making the fitness app more fun can encourage consumers to adopt and participate in physical activity, making it more social can be more effective in helping them sustain a walking routine in their daily living.